Screening for occult malignancy with FDG‐PET/CT in patients with unprovoked venous thromboembolism. Issue 9 (29th May 2013) - Alfonso, Ana; Redondo, Margarita; Rubio, Tomás; Del Olmo, Beatriz; Rodríguez‐Wilhelmi, Pablo; García‐Velloso, María J.; Richter, José A.; Páramo, José A.; Lecumberri, Ramón
<x xml:space="preserve">Abstract</x> Extensive screening strategies to detect occult cancer in patients with unprovoked venous thromboembolism (VTE) are complex and no benefit in terms of survival has been reported. FDG‐PET/CT (2‐[F‐18] fluoro‐2‐deoxy‐D‐glucose positron emission tomography combined with computed tomography), a noninvasive technique for the diagnosis and staging of malignancies, could be useful in this setting. Consecutive patients ≥ 50 years with a first unprovoked VTE episode were prospectively included. Screening with FDG‐PET/CT was performed 3–4 weeks after the index event. If positive, appropriate diagnostic work‐up was programmed. Clinical follow‐up continued for 2 years. Blood samples were collected to assess coagulation biomarkers. FDG‐PET/CT was negative in 68/99 patients (68.7%), while suspicious FDG uptake was detected in 31/99 patients (31.3%). Additional diagnostic work‐up confirmed a malignancy in 7/31 patients (22.6%), with six of them at early stage. During follow‐up, two patients with negative FDG‐PET/CT were diagnosed with cancer. Sensitivity (S), positive (PPV) and negative predictive values (NPV) of FDG‐PET/CT as single tool for the detection of occult malignancy were 77.8% (95% CI: 0.51–1), 22.6% (95% CI: 0.08–0.37) and 97.1% (95% CI: 0.93–1), respectively. Median tissue factor (TF) activity in patients with occult cancer was 5.38 pM vs. 2.40 pM in those without cancer (p = 0.03). Limitation of FDG‐PET/CT screening to patients with TF activity > 2.8 pM would improve the PPV to 37.5% and reduce the costs of a single cancer diagnosis from 20, 711€ to 11, 670€. FDG‐PET/CT is feasible for the screening of occult cancer in patients with unprovoked VTE, showing high S and NPV. The addition of TF activity determination may be useful for patient selection.